Effects of immersive virtual reality on sensory overload in a random sample of critically ill patients - Naef, Aileen C.; Gerber, Stephan M.; Single, Michael; Müri, René M.; Haenggi, Matthias; Jakob, Stephan M.; Jeitziner, Marie-Madlen; Nef, Tobias (Frontiers in Medicine, 2023)
Background Sensory overload and sensory deprivation have both been associated with negative health outcomes in critically ill patients. While there is a lack of any clear treatment or prevention strategies, immersive virtual reality is a promising tool for addressing such problems, but which has not been repetitively tested in random samples. Therefore, this study aimed to determine how critically ill patients react to repeated sessions of immersive virtual reality. Methods This exploratory study was conducted in the mixed medical–surgical intermediate care unit of the University Hospital of Bern (Inselspital). Participants (N = 45; 20 women, 25 men; age = 57.73 ± 15.92 years) received two immersive virtual reality sessions via a head-mounted display and noise-canceling headphones within 24 h during their stay in the unit. Each session lasted 30-min and showed a 360-degree nature landscape. Physiological data were collected as part of the participants’ standard care, while environmental awareness, cybersickness, and general acceptance were assessed using a questionnaire designed by our team (1 = not at all, 10 = extremely). Results During both virtual reality sessions, there was a significant negative linear relationship found between the heart rate and stimulation duration [first session: r(43) = −0.78, p < 0.001; second session: r(38) = −0.81, p < 0.001] and between the blood pressure and stimulation duration [first session: r(39) = −0.78, p < 0.001; second session: r(30) = −0.78, p < 0.001]. The participants had a high comfort score [median (interquartile range IQR) = 8 (7, 10); mean = 8.06 ± 2.31], did not report being unwell [median (IQR) = 1 (1, 1); mean = 1.11 ± 0.62], and were not aware of their real-world surroundings [median (IQR) = 1 (1, 5); mean = 2.99 ± 3.22]. Conclusion The subjectively reported decrease in environmental awareness as well as the decrease in the heart rate and blood pressure over time highlights the ability of immersive virtual reality to help critically ill patients overcome sensory overload and sensory deprivation. Immersive virtual reality can successfully and repetitively be provided to a randomly selected sample of critically ill patients over a prolonged duration.